PENGARUH PENGGUNAAN SISTEM INFORMASI REGISTRASI DIKLAT TERHADAP KEPUASAN PESERTA LATIH DI BAPELKES BATAM - Jurnal Ilmiah Manajemen UPB (Universitas Putera Batam, 2017)
With advances in technology-enabled in this modern era, Bapelkes Batam create an information system database called the Registration system of education and training, to facilitate the participants to register for training. so that participants do not need to fill out a paper form and in the form of leaflets. This study aims to determine the effect associated with the satisfaction of trainees in facilitating informed abou the biogrphical data and to select the training package. The samples used were all participants in the training Bapelkes. The method used is descriptive method with quantitative approach that studies using numeric data (numbers), which is then processed and analyzed to be concluded. With that conclusion that the training Registration Information System has been perceived as very beneficialto trainees in Bapelkes Batam. Satisfaction trainees Bapelkes perceived benefit to Batam. Registration Information System training positive effect on satisfaction of trainees in Bapelkes Batam.